Cover Image. Issue 2 (7th May 2018) - Muthukrishnan, Subbaratnam; Arakane, Yasuyuki; Yang, Qing; Zhang, Chuan‐Xi; Zhang, Jianzhen; Zhang, Wenqing; Moussian, Bernard
Abstract : On the cover : The cover image, by Subbaratnam Muthukrishnan et al., is based on the Article Future questions in insect chitin biology: A microreview, DOI:10.1002/arch.21454 .